Response of Junior High School Students on Online Learning in Suppressing the Spread of COVID-19 - Azhar, Fa’iz Muhammad; Maryanti, Rina (Bumi Publikasi Nusantara, 2023)
The purpose of this study was to determine the response of junior high school students to online learning in suppressing the spread of COVID-19. This study uses a descriptive method with a qualitative approach. Data collection techniques using online questionnaires. The questionnaire consists of several question points regarding online learning. The questionnaire was distributed in the form of a google form link via Whatsapp Group. The target respondents in this study were 52 students. Based on the results of student responses, most students responded well to the implementation of online learning. Students' understanding of the learning material delivered by the teacher during online learning can be understood by most students. A small number of students are supported by their parents in the implementation of online learning. The average duration of students carrying out online learning in a day is 3-4 hours. Most of the students’ responses to online learning stated that they could not interact with the teacher directly, which made it difficult for students to carry out online learning. Therefore, in dealing with online learning difficulties faced by students, a more interactive online learning media is needed, so that the level of interaction between teachers and students online can be the same as the level of student interaction offline.